Digital Storytelling Trends in Early Childhood Education in Indonesia: A Systematic Literature Review - Purnama, Sigit; Ulfah , Maulidya; Ramadani , Laili; Rahmatullah , Bahbibi; Ahmad , Iqbal Faza (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
Digital storytelling is often used in various contexts today, especially in the world of education. Many educators have followed this trend in early childhood education (ECE). This study examines the application of digital storytelling in ECE in Indonesia. Using a systematic literature review (SLR) a method, this research is a qualitative approach which is also known as a meta-synthesis. The literature reviewed was 15 articles from 56 articles that researchers found in the Google Scholar database. The results show that digital storytelling serves as an important method and medium to ensure children's learning experiences are enjoyable. In general, it is used in ECE in Indonesia through simple technology. This technology can enhance a story or fairy tale by making it more fun, interesting, communicative, and dramatic. However, the findings of this review of studies and methodological gaps have implications for ECE policy, practice, and research in Indonesia. Keywords: digital storytelling, early childhood education, storytelling trend in Indonesia References: Agosto, D. E. (2016). Why storytelling matters: Unveiling the literacy benefits of storytelling. Children and Libraries, 14(2), 21–26. Ahmad, I. F. (2022). Urgensi Literasi Digital di Indonesia pada Masa Pandemi COVID-19: Sebuah Tinjauan Sistematis. Nusantara: Jurnal Pendidikan Indonesia, 2(1), 1–18. https://doi.org/10.14421/njpi.2022.v2i1-1 Aisha, I., & Kaloeti, D. V. S. (2021). Digital Storytelling Intervention on Prosocial Behavior Improvement among Early Childhood. Psympathic: Jurnal Ilmiah Psikologi, 7(2), 185–196. https://doi.org/10.15575/psy.v7i2.5713 Boltman, A., & Druin, A. (2001). Children’s storytelling technologies. Differences in Elaboration and Recall. Chambers, G. J., & Yunus, M. M. (2017). Enhancing Learners’ Sentence Constructions via ‘Wheel of Grammar’. Pertanika Journal of Social Sciences & Humanities, 25(4). Davies, D., Jindal-Snape, D., Collier, C., Digby, R., Hay, P., & Howe, A. (2013). Creative learning environments in education—A systematic literature review. Thinking Skills and Creativity, 8, 80–91. Demirbaş, İ., & Şahin, A. (2020). A Systemic Analysis of Research on Digital Storytelling in Turkey. International Journal of Progressive Education, 16(4), 45–65. https://doi.org/10.29329/ijpe.2020.268.4 Dixon-Woods, M. (2010). Systematic reviews and qualitative methods. Qualitative Research: Theory, Method, and Practice. 3rd Edn. London: Sage, 331–346. Egan, K. (1989). Teaching as storytelling: An alternative approach to teaching and curriculum in the elementary school. University of Chicago Press. Gagné, R. M., Briggs, L. J., & Wager, W. W. (1988). Principles of Instructional Design. Holt, Rinehart, and Winston. https://books.google.co.id/books?id=dAsmAQAAIAAJ Gough, D. (2007). Weight of evidence: A framework for the appraisal of the quality and relevance of evidence. Research Papers in Education, 22(2), 213–228. Karlina, D. N., Widiastuti, A. A., & Soesilo, T. D. (2018). Meningkatkan Kemampuan Berbicara Anak Tk B Usia 5-6 Tahun Melalui Digital Storytelling di TK Apple Kids Salatiga. JPUD - Jurnal Pendidikan Usia Dini, 12(1), 1–11. https://doi.org/10.21009//jpud.121.01 Kearney, M., Jones, G., & Roberts, L. (2012). An Emerging Learning Design for Student-Generated